2020
DOI: 10.1177/1094670519898521
|View full text |Cite
|
Sign up to set email alerts
|

Mix&Match: A Resource-Based Complaint Recovery Framework for Tangible Compensation

Abstract: Resource exchange theory suggests service recovery compensation is optimal when it is commensurate with what was lost (e.g., refund for overcharging). However, in practice, companies cannot always follow the theory-driven prescriptions, and the complaint recovery literature remains silent on how to best recover in such suboptimal situations. This study takes a resource-based theory stance to propose Mix&Match, a complaint recovery framework for tangible compensation offers (refunds, redeliveries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Dialogic communication can thus help develop more positive perceptions and attitudes for the brand and result in improved brand attitudes and purchase intentions (Colliander et al, 2015). Scholars have generally agreed that attending to consumers' negative eWOM is an expected step of reputation recovery and relationship restoration (Gunarathne et al, 2017;Stakhovych and Tamaddoni, 2020). However, more research is needed.…”
Section: Expectancy Violation and Brand Feedback To Negative Ewommentioning
confidence: 99%
See 4 more Smart Citations
“…Dialogic communication can thus help develop more positive perceptions and attitudes for the brand and result in improved brand attitudes and purchase intentions (Colliander et al, 2015). Scholars have generally agreed that attending to consumers' negative eWOM is an expected step of reputation recovery and relationship restoration (Gunarathne et al, 2017;Stakhovych and Tamaddoni, 2020). However, more research is needed.…”
Section: Expectancy Violation and Brand Feedback To Negative Ewommentioning
confidence: 99%
“…A review of negative eWOM recovery strategies found that brands offer tangible compensation (i.e. refunds, credits) for optimal recovery after a brand failure (Stakhovych and Tamaddoni, 2020). Per resource exchange theory (RET; Foa and Foa, 1974), when a brand's performance fails, consumers experience a loss of resources (e.g.…”
Section: Compensationmentioning
confidence: 99%
See 3 more Smart Citations